2018
DOI: 10.1038/s41467-018-06975-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and assembly of colloidal cuboids with tunable shape biaxiality

Abstract: The design and assembly of monodisperse colloidal particles not only advances the development of functional materials, but also provides colloidal model systems for understanding phase behaviors of molecules. This communication describes the gram-scale synthesis of highly uniform colloidal cuboids with tunable dimension and shape biaxiality and their molecular mesogen-like assembly into various mesophasic structures in pristine purity. The synthesis relies on the nanoemulsion-guided generation of ammonium sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…After equilibrating the sample overnight, a characteristic nematic texture was seen ( Fig. 3 D, Inset) (37,38). No focal conical defect or oily streak defect, typical defects for smectic or cholesteric phase, was observed.…”
Section: Significancementioning
confidence: 98%
“…After equilibrating the sample overnight, a characteristic nematic texture was seen ( Fig. 3 D, Inset) (37,38). No focal conical defect or oily streak defect, typical defects for smectic or cholesteric phase, was observed.…”
Section: Significancementioning
confidence: 98%
“…Preparation of net-poly(MA-11-2-11-MA)-co-(MA-11-RhB) capsules Silica microrods and microboards were synthesized according to previous reports (39,40). Silica microspheres were commercially purchased.…”
Section: Synthesis Of Pyr-eo 4 -Nmentioning
confidence: 99%
“…The study of entropically-driven phase transitions in liquid crystals has been an active field of research from the pioneering work of Onsager 1 , having a major boost in the 80's and 90's [2][3][4][5][6][7] and continuing as a very active topic of research up to the present [8][9][10][11][12][13][14][15][16][17][18] . These works theoretically and experimentally showed that liquid-crystalline uniform phases, such as uniaxial or biaxial nematics (N), and non-uniform phases such as smectic and columnar phases, can be stabilized solely by extremely shortranged repulsive particle interactions.…”
Section: Introductionmentioning
confidence: 99%